Yellow carrot (Daucus carota L.), a biotechnological food for cows - Díaz-Monroy, Byron; Chacha, Elvita; Baquero, Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Agro-industrial residues of carrots along with whey were evaluated and used to prepare bio-silage for cows. Physical, bromatological and microbiological analyzes were carried out. Four treatments (different concentrations of native-probiotic microbial preparation) were used with 2%, 4%, 6%, and 8%. The pH of the process was 3.9 and the temperature was 19 °C. The treatment with 6% of probiotic yielded the best results, with 15.39% of protein, 74.78% of humidity and 14.04% of fiber, free of pathogens like Salmonella sp., Clostridium sp., Escherichia coli and molds, with and a high concentration of lactic acid bacteria (2.40E + 04 UFC.ml-1) and a cost benefit of 1.33. Milk production in crossbred Holstein cows fed with this product increased from 14.08 to 17.40 L.day-1, so we recommended using it as supplementary feed.